a Atraksi Batamoe Sebagai Daya Ungkit Pertumbuhan Desa Wisata Bilibante: Inovasi Atraksi Pariwisata - Fathurrahman; Triana Lidona Aprilani; Muhammad Habibullah Aminy; Suci Emilia Fitri; Pahrul Azim (Research and Development Agency Ministry of Home Affairs, 2025)
Village tourism is an important element in the development of a sustainable tourism industry in Indonesia. The success of tourism village development is strongly influenced by the presence of unique attractions based on local culture, natural beauty, and social values upheld by the local community. This research will investigate the role of unique attractions, such as the Betemoe Package in Bilebante Tourism Village, in encouraging local economic growth, cultural preservation, and strengthening community social cohesion. Furthermore, some attractions, like the Betemoe Package in Bilebante Tourism Village, aim to educate tourists and offer authentic cultural and religious interactions. In addition, there has been no comprehensive research on how the integration of multi-stakeholder support, local community participation, and local wisdom-based marketing approaches can strengthen the competitiveness of tourism villages. This research uses a qualitative approach with a case study approach with observation techniques, in-depth interviews, and documentation. The main focus of the research is on the active involvement of local communities, strengthening the role of traditional culture, and local wisdom-based marketing strategies in creating authentic and meaningful tourism experiences. The results indicate that the Betemoe Package not only offers entertainment through traditional dance arts and the reading of lontar manuscripts but also educates tourists about the values of tolerance and interfaith harmony, especially between Muslims and Hindus who coexist harmoniously. These attractions have proven to be able to strengthen the cultural identity of the community while increasing collective awareness of the importance of preserving ancestral heritage. In addition, the synergy between the village government, tourism awareness groups (Pokdarwis), MSME players, and the private sector is a key factor in strengthening infrastructure, expanding promotion, and increasing the competitiveness of tourist villages. In conclusion, the development of tourist attractions based on local culture and active community participation can create a tourism ecosystem that is inclusive, sustainable, and has a real impact on the social and economic welfare of village communities.